2020
DOI: 10.1111/jnc.15174
|View full text |Cite
|
Sign up to set email alerts
|

Distinct alpha‐Synuclein species induced by seeding are selectively cleared by the Lysosome or the Proteasome in neuronally differentiated SH‐SY5Y cells

Abstract: A major pathological feature of Parkinson's disease (PD) is the aberrant accumulation of misfolded assemblies of alpha-synuclein (α-Syn). Protein clearance appears as a regulator of the ''α-Syn burden" underlying PD pathogenesis. The picture emerging is that a combination of pathways with complementary roles, including the Proteasome System and the Autophagy-Lysosome Pathway, contributes to the intracellular degradation of α-Syn. The current study addresses the mechanisms governing the degradation of α-Syn spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 61 publications
2
20
0
Order By: Relevance
“…The limited detection of pS129 aSyn inclusions suggests that aggregation precedes the pathological accumulation of pS129 aSyn deposits, as previously reported using an inducible model of seeding in SH-SY5Y cells. In this study, the formation of insoluble pS129 aSyn inclusions was observed when a higher amount of brils was applied to the cells and for a longer incubation period [22]. Consistently, we found that application of lower amount of PFFs rarely resulted in the detection of pS129 aSyn positive aggregates (data not shown).…”
Section: Discussionsupporting
confidence: 80%
“…The limited detection of pS129 aSyn inclusions suggests that aggregation precedes the pathological accumulation of pS129 aSyn deposits, as previously reported using an inducible model of seeding in SH-SY5Y cells. In this study, the formation of insoluble pS129 aSyn inclusions was observed when a higher amount of brils was applied to the cells and for a longer incubation period [22]. Consistently, we found that application of lower amount of PFFs rarely resulted in the detection of pS129 aSyn positive aggregates (data not shown).…”
Section: Discussionsupporting
confidence: 80%
“…To eliminate the complexities associated with in vivo studies, including the pharmacokinetic behavior of tested compounds, and minimized data variabilities among individual animals, we used cultured neuronal cells, SH-SY5Y, instead of whole animals. SH-SY5Y cells are well established as model neurons to study neuroprotection and neurodegenerative mechanisms [ 41 , 57 , 58 ], and are widely used to study autophagy and UPS [ 59 , 60 , 61 , 62 ]. Interestingly, we found that lithium chloride and rilmenidine promoted cell protection, whereas rapamycin and Torin-1 exacerbated cell death in SH-SY5Y neuroblastoma cells exposed to proteasome inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…As we observed a significant increase in αSyn levels in all neuronal districts, the DOPAL-induced alterations in the live-cell time-lapse imaging experiments potentially derived from a combination of an impaired mobility of αSyn along the neurites and a decreased degradation efficiency both in the periphery and the soma, where different pathways are involved. At synaptic level, αSyn monomers and small on-pathway oligomers are known to be degraded by the UPS and local proteases, whereas in the cell body the autophagic pathway participate as additional backup, especially for the clearance of larger aggregates 44 . Interestingly, this might be reflected by the αSyn half-lives that we estimated in the two different regions in the live imaging with Nocodazole, where the αSyn turnover was about 2.5 times longer in the periphery as compared to the soma.…”
Section: Discussionmentioning
confidence: 99%